Relationship between Detector Size and the Need for Extra Images and their Effect on Radiation Exposure in Digital Mammography Screening - Entz, K.; Sommer, A.; Heindel, W.; Lenzen, H. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To determine the number of extra images (EI) that are necessary for imaging large breasts when using a detector smaller than 24 cm × 30 cm and to calculate the additional average glandular dose (AGD) for these images.Materials and Methods: The screening mammograms taken between 2007 and 2011 were assessed for a photon counting full-field digital mammography (PCM) system (detector size: 24 cm × 26 cm) and a computed radiography (CR) system (24 cm × 30 cm). The number of EI was recorded and the AGD calculated. This AGD was compared with the mean AGD of 47 conventional full-field digital mammography (FFDM) systems.Results: A total of 62,466 examinations were analyzed. EI had to be taken in 0.6 % (199/32,766) of all PCM examinations and 0.3 % (90/29 700) of all CR examinations. This corresponded to a total of 327 and 191 EI for the PCM and CR systems, respectively. More than one quarter of the examinations with EI were necessary because the breast was not properly positioned in the original image (PCM 31 %, CR 29 %). The mean AGD per EI was 0.7 ± 0.1 mGy for the PCM and 2.6 ± 1.2 mGy for the CR system. The mean AGD for all breast thicknesses for FFDM was 1.4 ± 0.3 mGy.Conclusion: In general, large breasts cannot be imaged with just one image per view. The number of examinations where EI are needed is doubled with the 24 cm × 26 cm detector of the PCM system. However, the absolute number is small. The total dose, as the sum of the original and the EI, is equal to the mean AGD of a single image of the FFDM systems and lower than the dose of a single image with the CR system.Key Points:• When imaging large breasts, extra images are also needed on standard detectors.• The rate of examinations with extra images is doubled with a 24 cm × 26 cm format of a photon counting mammography (PCM) system.• The absolute number of extra images required due to detector size is small.• The total dose (sum of original and extra image) of PCM is below dose limits.Citation Format:• Entz K, Sommer A, Heindel W et al. Relationship between Detector Size and the Need for Extra Images and their Effect on Radiation Exposure in Digital Mammography Screening. Fortschr Röntgenstr 2014; 186: 868 – 875
Keywords: detector size; mammography screening; digital mammography; average glandular dose; photon counting